Narrative comprehension and production abilities of children with 22q11.2 deletion syndrome. (December 2021) - Selten, Iris; Boerma, Tessel; Everaert, Emma; Vansteensel, Mariska J.; Vorstman, Jacob; Wijnen, Frank
Highlights: School-aged children with 22q11DS showed impaired narrative abilities. Their narrative comprehension seemed more affected than narrative production. Narrative abilities in 22q11DS were comparable to those observed in DLD. Comprehension difficulties were not entirely explained by low intellectual ability. Abstract: Background: The 22q11.2 Deletion Syndrome (22q11DS) is associated with language deficits and weak intellectual functioning. In other clinical groups, linguistic and cognitive difficulties have been associated with impaired acquisition of narrative abilities. However, little is known about the narrative abilities of children with 22q11DS. Aims: To describe the ability of children with 22q11DS to produce and comprehend narrative macrostructure. Additionally, to examine the role of intellectual functioning in explaining their narrative difficulties. Methods and procedures: Narrative skills of 14 school-aged children with 22q11DS were compared to those of younger typically developing (TD) children matched on mental age and same-aged peers with Developmental Language Disorder (DLD). Outcomes and results: Children with 22q11DS had significantly lower scores on narrative comprehension than younger TD children. No significant differences emerged on narrative production. Children with 22q11DS and children with DLD did not differ significantly on any of the narrative measures. Conclusions and implications: Narrative comprehension in children with 22q11DS seems more affected than production. Narrative comprehension difficulties cannot be entirely explained by a low level of intellectual functioning. Narrative comprehension and production abilities in 22q11DS require further consideration.